1981
DOI: 10.1128/jvi.38.2.761-769.1981
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of JC virus DNA purified directly from human progressive multifocal leukoencephalopathy brains

Abstract: Human polyomavirus JC DNA was purified directly from the diseased brain tissue of two patients with progressive multifocal leukoencephalopathy (PML) by a method employing differential salt precipitation (B. Hirt, J. Mol. Biol. 26:365-369, 1967). Each of the viral genomes (JC-NIH-1 and JC-NIH-2) was molecularly cloned intact in Escherichia coli, using pBR322, at their unique EcoRI (0.00 map unit) and BamHI (0.51 map unit) sites. The JC-NIH-1 genome was approximately 50 base pairs larger and the JC-NIH-2 genome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
0

Year Published

1982
1982
1998
1998

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 39 publications
2
17
0
Order By: Relevance
“…The results discussed above suggest that the heterogeneity of the JCV DNA, observed when PML samples have been passaged in cell culture, is largely, but probably not entirely, the result of in vitro passage. The minor species of smaller supercoiled DNA obtained directly from one patient (228) indicates that viral heterogeneity might also be a factor in PML. Nevertheless, although viral defectiveness might in part account for slow viral replication and cytopathogenesis, more brain samples will have to be analyzed directly to determine whether viral heterogeneity plays a role in the pathogenesis of PML.…”
Section: Bk Virus (Bkv)mentioning
confidence: 96%
See 1 more Smart Citation
“…The results discussed above suggest that the heterogeneity of the JCV DNA, observed when PML samples have been passaged in cell culture, is largely, but probably not entirely, the result of in vitro passage. The minor species of smaller supercoiled DNA obtained directly from one patient (228) indicates that viral heterogeneity might also be a factor in PML. Nevertheless, although viral defectiveness might in part account for slow viral replication and cytopathogenesis, more brain samples will have to be analyzed directly to determine whether viral heterogeneity plays a role in the pathogenesis of PML.…”
Section: Bk Virus (Bkv)mentioning
confidence: 96%
“…Unfortunately, this instability also implies that one cannot use stocks of PML isolates which have been amplified by in vitro passages to determine whether defectives were present in the initial isolate. In recognition of this problem, JCV DNA was purified directly from the brains of two PML patients and cloned in E. coli by using the vector pBR322 (228). Uncloned and unpassaged JCV DNA from one of the isolates showed a minor band upon electrophoretic analysis, indicating that it might be heterogeneous in size.…”
Section: Bk Virus (Bkv)mentioning
confidence: 99%
“…Consequently, JCV establishes a persistent infection in the kidney. Unlike the Mad-1 regulatory-region sequences found predominantly in JCV isolated from the brains of PML patients (15,19,28,34), JCV isolated from urine has the "archetype" regulatory-region sequence arrangement (14,(40)(41)(42). Variations in the genomic sequences within the VP1 structural protein region have also been reported and have been used in some studies to classify different JCV genotypes (1)(2)(3)25).…”
mentioning
confidence: 99%
“…However, there have been a few documented cases in which PML occurred in patients with no sign of immunological disorders (18). Among JCV isolates from PML patients there exists a remarkable diversity in the structures of the regulatory regions on the genomes, although the structures of the other regions are apparently conserved (4,6,(10)(11)(12)(13)16). Dorries (4), who analyzed JCV DNA from the brain and kidney of the same PML patient, suggested that initial infection with one JCV strain was followed by the development of variants differing in regulatory sequences.…”
mentioning
confidence: 99%